Paradoks Atas Implementasi Peraturan Presiden Nomor 55 Tahun 2019 Terkait Pertambangan Nikel Dan Upaya Perlindungan Lingkungan Di Kabupaten Konawe Utara Sulawesi Tenggara - Adiva Resqita Maidina; Sukri Tamma (Politik Islam, 2023)
This paper aims to show the implementation of Presidential Regulation no. 55 of 2019 concerning Presidential Decree concerning the Acceleration of the Battery Electric Vehicle Program for Road Transportation. This policy is a form of effort to maintain environmental stability in order to create clean air quality and minimal emissions. Battery-based electric vehicles can reduce carbon emissions which have been polluting the environment. The manufacture of battery-based electric vehicles is required to use the Domestic Component Level (TKDN) in its manufacture, one of which is Nickel. As a consequence of its implementation, nickel mining has grown massively in Indonesia, including in North Konawe Regency to meet the use of domestic components. This opens up space for interaction related to interests, power, resources related of nickel mining management and its relation to environmental conditions around the mine. At the end, there is still a condition of environmental damage that occurs as implication of Nickel mining which is basically a condition that is not in line with the objectives of the Policy which seeks to maintain environmental conditions